2017
DOI: 10.1097/igc.0000000000000977
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Pegylated Liposomal Doxorubicin in Low-Grade Serous Ovarian Carcinoma

Abstract: Pegylated liposomal doxorubicin is relatively active in LGSOC. The treatment of stable disease resulted in increase in PFS in 78.6% of patients by a mean of 350%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Rose et al reported a complete response rate of 14.3%. The treatment of stable disease by PLD resulted in increased PFS in 78.6% of cases, by an average of 350% [ 89 ]. The addition of bevacizumab to chemotherapy for recurrent LGSC might enhance response rates.…”
Section: Managementmentioning
confidence: 99%
“…Rose et al reported a complete response rate of 14.3%. The treatment of stable disease by PLD resulted in increased PFS in 78.6% of cases, by an average of 350% [ 89 ]. The addition of bevacizumab to chemotherapy for recurrent LGSC might enhance response rates.…”
Section: Managementmentioning
confidence: 99%
“…Median time to progression was 34.7 weeks (range: 4.3 – 232.4 weeks) for platinum-sensitive patients and 26.4 (range: 8.4 – 149 weeks) for platinum-resistant patients. Pegylated liposomal doxorubicin (PLD) seems to be the most active regimen for LGSOC 29 . There is no data which compares the different regimens for platinum-based therapy to treat LGSOC.…”
Section: Reviewmentioning
confidence: 99%
“…[50] In vitro experimental studies have shown that LGSOC has strong resistance to paclitaxel, carboplatin, cisplatin, cyclophosphamide, and gemcitabine and weak resistance to etoposide, adriamycin, and topotecan. [49] Rose et al [51] evaluated 21 LGSOC patients with PLD application and found that 3 patients (14.3%) achieved CR after the application of PLD, 67% of the patients had stable disease, and the response rate to PLD was independent of platinum sensitivity. PLD showed good application prospects.…”
Section: Chemotherapymentioning
confidence: 99%